GUARANTEE OF THE APPLICATION OF CAPITAL PUNISHMENT ON A PEACEFULL AND HARMONIOUS LIFE - Tajul Arifin (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2019)
The application of capital punishment has become worldwide debate. European human rights have abolished the capital punishment in their legal system. However, some countries, including United States, have still established the capital punishment. In some Asia countries have still implemented capital punishment, including China, Indonesia, and Saudi Arabia. Those countries have received a significant benefit from the implementation of capital punishment. In this article, author will explore some benefit of capital punishment to create a peaceful and harmonious life. To create basic understanding, author have used theoretical background on crime-punishment connection. Author has also examined the restraining effects of the application of capital punishment on crime in several countries, and presenting some quantitative data. The final segment has displayed a fleeting discussion, and offering some generalizations. The purpose provides a clear conclusion, referred on the practice of various countries. This experience will have a significant benefit for development Islamic law in Aceh, Indonesia. Abstrak: Penerapan hukuman mati telah menjadi perdebatan di seluruh dunia. Badan hak asasi manusia Eropa telah menghapuskan hukuman mati dari sistem hukum mereka. Namun, beberapa negara, termasuk Amerika Serikat, masih menerapkan hukuman mati. Beberapa negara Asia juga masih menerapkan hukuman mati, termasuk Cina, Indonesia, dan Arab Saudi. Negara-negara tersebut telah mendapatkan manfaat yang signifikan dari penerapan hukuman mati. Dalam artikel ini, penulis akan mengeksplorasi beberapa manfaat hukuman mati dalam menciptakan kehidupan yang damai dan harmonis. Untuk membangun pemahaman dasar, penulis menggunakan latar belakang teoretis mengenai koneksi antara kejahatan dan hukuman. Penulis juga menyelidiki dampak pembatasan penerapan hukuman mati pada kejahatan di beberapa negara, dan menyajikan data kuantitatif. Segmen terakhir dari artikel ini menyajikan diskusi singkat, dan beberapa generalisasi, dengan tujuan untuk memberikan kesimpulan yang jelas berdasarkan praktik di berbagai negara. Pengalaman ini sangat bermanfaat untuk pengembangan hukum Islam di Aceh, Indonesia. Kata Kunci: Hukuman Mati, Teori Kejahatan, Hukum Pidana Islam